Intravesical prostatic protrusion as a predictor of early urinary continence recovery after laparoscopic radical prostatectomy. (27th March 2014) - Lee, Chan Ho; Ha, Hong Koo
<x xml:space="preserve">Abstract</x> Objectives To evaluate the significance of intravesical prostatic protrusion as a predictor of early urinary continence recovery after laparoscopic radical prostatectomy. Methods A total of 242 patients who underwent laparoscopic radical prostatectomy were included in the study. Data on incontinence status and the number of pads required per day for urinary incontinence were collected. Urinary continence was defined as no pad use or occasional security pad use. Intravesical prostatic protrusion was measured by the vertical distance from the tip of the protruding prostate to the base of the urinary bladder in the sagittal plane of preoperative magnetic resonance imaging. Continence at 1, 3, 6 and 12 months postoperatively was assessed by dividing the patients into two groups based on the degree of intravesical prostatic protrusion. The correlation between preoperative factors and urinary continence after laparoscopic radical prostatectomy was examined. Results The urinary continence rates at postoperative month 1, 3, 6 and 12 were 19%, 50%, 79.8% and 92.1%, respectively. In the multivariate logistic analysis, intravesical prostatic protrusion was a significant independent predictive factor of early urinary continence at 1, 3, 6, 9 and 12 months. Markedly improved urinary continence was observed in the non‐significant intravesical prostatic protrusion group (intravesical prostatic protrusion <5 mm) at all periods compared with the significant intravesical prostatic protrusion group (intravesical prostatic protrusion ≥5 mm; P < 0.05). Conclusions These findings suggest that the likelihood of postoperative urinary incontinence in patients undergoing laparoscopic radical prostatectomy is markedly higher in those with larger intravesical prostatic protrusion, and that intravesical prostatic protrusion is correlated with the duration of postoperative urinary incontinence.